Russula rubiginosus sp. nov. in Russula subsect. Maculatinae from Heilongjiang Province, Northeast China - Ji, Rui-Qing; Xie, Meng-Le; Zhou, Ji-Jiang; Meng, Li-Peng; Li, Yu; Zhang, Zhong-Hui; Li, Guo-Jie (Phytotaxa, 2022)
Russula rubiginosus sp. nov. (Subsect. Maculatinae) associated with Quercus mongolica is described and illustrated based on phylogenetic analyses of internal transcribed spacer (ITS) ribosomal DNA sequences and morphological evidence. This species is characterized by the rusty spots on the pileus and stipe, an acrid taste, a yellow spore print, smaller basidiospores, and abundant cystidia in pileipellis and stipitipellis. Furthermore, the morphological characteristics were described in detail and compared with R. globispora and R. subrubescens.